A brief review of the economic sociology of Taiwan's development - Zong-Rong Lee (economic sociology. perspectives and conversations, 2021)
Taiwan started its industrialization in the 1960s, when the government pushed development through regulating measures such as tax incentives and subsidies via foreign aid. The market then went through decades of rapid growth, with local businesses booming and becoming pivotal within the nexus of global production networks, marking Taiwan as one of the most successful late-developing economies. Between 1963 and 1996, the nation's GDP grew on average by more than 9 percent, establishing it as one of the four Asian tigers alongside Singapore, Hong Kong, and South Korea (Fei et al. 1979; World Bank 1993). The success of Taiwan's economy caught up with the revival of American interest in economic sociology that began in the 1980s. It was amidst this academic revival that Taiwan entered the stage of global economies and caught the attention of researchers, who shared one main concern: Why were Taiwan and its fellow East Asian neighboring societies able to shed their peripheral status? More so, how could they maintain economic growth for so long (Haggard 1990)? Many scholars noticed that the specific set of politico-economic conditions in Cold War geopolitics created a unique opportunity for the development of Taiwan (as well as Japan and South Korea). The then authoritarian Kuomintang (the Chinese Nationalist Party) government, which inherited the industrial infrastructure from the previous Japanese colonial regime, enforced a land reform that eradicated the potential political threat of landlords (Winckler and Greenhalgh 1988) and funneled capital extracted from the agricultural sectors to industrial projects and helping to build the foundation of industrial enterprises (Ka and Selden 1986). The state not only provided the required social stability for private actors to accumulate capital but also managed to link local production to demand from the US and Japanese markets, as well as to suppress quelling unrest among the working class and farmers, eventually fostering an export-oriented economy (Deyo 1987). (...)
Keywords: 300